A200 AN INTEGRATED ANALYSIS OF EFFICACY OF OBETICHOLIC ACID IN CANADIAN PATIENTS. (1st March 2018) - Mason, A; Vincent, C; Aspinall, A; Swain, M; Hirschfield, G M; Minuk, G; Shah, H; Owens-Grillo, J; Malecha, E Smoot; MacConell, L
Abstract: Background: Obeticholic acid (OCA) is a potent FXR agonist investigated for the treatment of primary biliary cholangitis (PBC) in 3 randomized, double-blind (DB), placebo (PBO)-controlled trials ± UDCA. Aims: This analysis pools data from all 3 trials to investigate the efficacy and safety of OCA in patients treated in Canada. Methods: Key Entry Criteria: ALP 1.5 to 10x ULN and conjugated bilirubin ≤2x ULN (Phase 2 trials, DB phase=3 months); ALP ≥1.67x ULN or total bilirubin >ULN but <2x ULN (Phase 3 trial, DB phase=12 months). Data were pooled and assessed at the end of DB treatment (EOT) for each trial. Patients receiving 5 or 10 mg OCA were pooled into a single group: ≤10 mg OCA. Results: Baseline (BL) biochemistry values were elevated in the ≤10 mg OCA group compared to the PBO group (Table 1). In patients receiving concomitant UDCA, there were significant reductions in ALP, ALT, and GGT at EOT compared to PBO. Total bilirubin and AST were reduced but not significant. Efficacy was similar in patients receiving OCA monotherapy. Pruritus was the most common adverse event, which occurred in 32% of PBO patients and 61% of patients receiving ≤10 mg OCA. Conclusions: Reductions in markers of cholestasis and hepatic damage with OCA treatment in Canadian patients were generally comparable to the global OCA treated population. Improvements in many of these markers have been associated with improved long-term outcomes in PBC. Funding Agencies: None